An overview: Reaping off the benefits of flexible working arrangements (FWAs) to both employer and employees - Nur Farina Mohamad; Fun, Nggik Ye Jenny; Ain Athira Sa’et; Huang Lishiyun; Sharija Che Shaari; Sharifah Rahama Amirul (Faculty of Business, Economics and Accountancy, 2021)
The Movement Control Order (MCO) was introduced as a Malaysian preventive measure against the COVID-19 virus outbreak. These drastic changes have compelled the majority of Malaysia's workforce to adopt flexible working arrangements (FWAs) which was not widely practised prior to pandemic crisis. Prior to the pandemic, FWAs is not widely practised in Malaysia. Therefore, this paper provides an overview summary from the existing FWAs related studies and reaping off the benefits of FWAs to both employer and employees. Through the realisation of the benefits of FWAs on both an individual and an organisational level, the significance of FWAs can be convincingly demonstrated, and employees and employers should not be hesitant to embrace FWAs while also adjusting to these prospects for future business success.